Effects of different fluid management on lung and kidney during pressure‐controlled and pressure‐support ventilation in experimental acute lung injury. Issue 17 (6th September 2022) - de Carvalho, Eduardo Butturini; Fonseca, Ana Carolina Fernandes; Magalhães, Raquel Ferreira; Pinto, Eliete Ferreira; Samary, Cynthia dos Santos; Antunes, Mariana Alves; Baldavira, Camila Machado; da Silveira, Lizandre Keren Ramos; Teodoro, Walcy Rosolia; de Abreu, Marcelo Gama; Capelozzi, Vera Luiza; Felix, Nathane Santanna; et al.
Abstract: Optimal fluid management is critical during mechanical ventilation to mitigate lung damage. Under normovolemia and protective ventilation, pulmonary tensile stress during pressure‐support ventilation (PSV) results in comparable lung protection to compressive stress during pressure‐controlled ventilation (PCV) in experimental acute lung injury (ALI). It is not yet known whether tensile stress can lead to comparable protection to compressive stress in ALI under a liberal fluid strategy (LF). A conservative fluid strategy (CF) was compared with LF during PSV and PCV on lungs and kidneys in an established model of ALI. Twenty‐eight male Wistar rats received endotoxin intratracheally. After 24 h, they were treated with CF (minimum volume of Ringer's lactate to maintain normovolemia and mean arterial pressure ≥70 mmHg) or LF ( 4 times higher than CF) combined with PSV or PCV (VT = 6 ml/kg, PEEP = 3 cmH2 O) for 1 h. Nonventilated animals ( n = 4) were used for molecular biology analyses. CF‐PSV compared with LF‐PSV: (1) decreased the diffuse alveolar damage score (10 [7.8–12] vs. 25 [23–31.5], p = 0.006), mainly due to edema in axial and alveolar parenchyma; (2) increased birefringence for occludin and claudin‐4 in lung tissue and expression of zonula‐occludens‐1 and metalloproteinase‐9 in lung. LF compared with CF reduced neutrophil gelatinase‐associated lipocalin and interleukin‐6 expression in the kidneys in PSV and PCV. In conclusion, CF compared with LF combined with PSV yielded less lung epithelial cell damage in the current model of ALI. However, LF compared with CF resulted in less kidney injury markers, regardless of the ventilatory strategy. Abstract : It is not yet known whether tensile stress can lead to comparable lung protection than compressive stress in acute lung injury (ALI) under a liberal fluid (LF) strategy. Thus the interaction between fluid and ventilator strategies was evaluated. Normovolaemia combined with pressure‐support ventilation yielded less lung epithelial cell damage compared with LF strategy in the current model of ALI. However, liberal compared with conservative fluid strategy resulted in less kidney injury markers, regardless of the ventilatory strategy.